Hyperbaric Oxygen Therapy for Carbon Monoxide-Induced Delayed Neuropsychiatric Sequelae: Case Report of Two Cases and Relevant Literature Review. (4th March 2021) - Monji, Akira; Tateishi, Hiroshi; Murakawa, Toru; Matsushima, Jun; Kunitake, Yutaka; Shiraishi, Takumi; Kojima, Ryohei; Inaba, Takayoshi; Kato, Takahiro; Mizoguchi, Yoshito
Abstract : We herein report two cases with carbon monoxide- (CO-) induced delayed neuropsychiatric sequelae (DNS) successfully treated with hyperbaric oxygen therapy (HBOT) in attempt suicide by charcoal burning. The two patients with CO-induced DNS were successfully treated with a total of more than 100 sessions of HBOT. Frontal assessment battery (FAB) was useful to examine the effectiveness of HBOT objectively. In the future study, a large-randomized trial is required to establish the efficacy of HBOT for the treatment of DNS.